Jazz and Visual Abstraction: The Artworks of Mongezi Ncaphayi - Kanyane, Thabang (Michaelis School of Fine Art, 2025)
This study aims to theorize the intersections between jazz music and abstraction in the visual arts. Its focus is to analyse phenomenological aspects in the selected works of South African contemporary visual artist and jazz saxophonist Mongezi Ncaphayi (b.1983), as a means to understand the nature of the relationship between the 'visual' and 'sonic' in his work. This includes: locating visual art practice within a wider constellation of imagery production, which I refer to as jazz visual culture, encompassing album cover art, photography, and graphic scores, to outline a culturally informed and constructed view of jazz and visual art practices. By paying particular attention to Ncaphayi's iconography and the explications of his work, this study aims to clarify the resonances between the visual and the sonic, while demonstrating the significance of both in the realm of signification. Although non-figurative abstraction lacks the conventional motifs found in figurative works, such as the depiction of instrumentation and portraiture, or even the symbolic stability of music notation, it continues to play a role in mediating the musical, aesthetic, and cultural meanings of jazz, despite its idiosyncrasy. This study is conducted by examining existing literature on jazz visual histories, criticism, music theory, and interviews with Mongezi Ncaphayi as research tools. Additionally, specific artworks are analysed to support an investigation of the cross- modal encounters between visual and sonic elements. These are then interpreted through the lenses of phenomenology, formalism, iconography, and black studies.